The crystallization of metal soaps and fatty acids in oil paint model systems - Hermans, Joen J; Keune, Katrien; van Loon, Annelies; Iedema, Piet D (Physical chemistry chemical physics : PCCP, 2016)
The formation and crystallization of metal soaps in oil paint layers is an important issue in the conservation of oil paintings. The chemical reactions and physical processes that are involved in releasing metal ions from pigments and fatty acids from the oil binder to form crystalline metal soap deposits have so far remained poorly understood. We have used a combination of differential scanning calorimetry (DSC) and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) on model mixtures of palmitic acid, lead palmitate or zinc palmitate and linseed oil to study the transition from amorphous material to crystalline fatty acid or metal soap. This transition forms the final stage in the cascade of processes leading to metal soap-related oil paint degradation. Palmitic acid as well as the metal soaps showed nearly ideal solubility behavior. However, it was found that, near room temperature, both lead and zinc palmitate are practically insoluble in both liquid and partially polymerized linseed oil. Interestingly, the rate of metal soap and fatty acid crystallization decreased rapidly with the degree of linseed oil polymerization, possibly leading to systems where metal soaps are kinetically trapped in a semi-crystalline state. To explain the various morphologies of metal soap aggregates observed in oil paint layers, it is proposed that factors affecting the probability of crystal nucleation and the rate of crystal growth play a crucial role, like exposure to heat or cleaning solvents and the presence of microcracks.